MODERNIZING ISLAMIC RELIGIOUS EDUCATION: BRIDGING TRADITION AND 21ST-CENTURY SKILLS THROUGH CURRICULUM AND TECHNOLOGY INTEGRATION - Latifah, Endah Nur; Zamroni, Zamroni; hefniy, hefniy; Tamam, Badrut (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
In the modern era, education plays a vital role in preparing students to navigate an interconnected and technologically advanced world. Islamic Religious Education (PAI) is crucial for fostering moral and spiritual development among Muslim students. However, the current curriculum often fails to address 21st-century competencies such as critical thinking, digital literacy, and global citizenship. This study examines the alignment of the PAI curriculum with future generational needs, the integration of technology in Islamic education, and the gaps between traditional content and modern educational demands. Using interviews, classroom observations, surveys, and focus group discussions, the research highlights both the strengths and limitations of the curriculum. This study proposes a comprehensive reform approach that balances traditional Islamic principles with modern pedagogical practices. Key recommendations include curriculum updates to incorporate 21st-century skills, professional development for educators, and investments in digital infrastructure. By adopting these measures, Islamic Religious Education can evolve to empower students as morally grounded, critical thinkers, and global citizens, ensuring its relevance in the 21st century.